The Healthy Body Image Intervention and Reduction in Eating Disorder Symptomatology and Muscle Building Supplement Use in High School Students: A Study of Mediating Factors - Svantorp-Tveiten, Kethe Marie Engen; Ivarsson, Andreas; Torstveit, Monica Klungland; Sundgot-Borgen, Christine; Mathisen, Therese Fostervold; Bratland-Sanda, Solfrid; Rosenvinge, Jan Harald; Friborg, Oddgeir; Pettersen, Gunn; Sundgot-Borgen, Jorunn (Frontiers in Psychology, 2022)
Background: Mediation analysis is consequential for testing the theoretical framework underpinning an intervention. Accordingly, we aimed to investigate if the Healthy Body Image (HBI) intervention’s effect on eating disorder (ED) symptomatology and the use of muscle building supplements was mediated by the change in risk- and protective factors for ED development and muscle building supplement use. Methods: This study used data from the HBI intervention: a cluster randomized controlled universal intervention, involving 30 schools in Norway, aimed at promoting positive-body image and embodiment and reducing the risk for ED development. Overall, 1,713 adolescents (of which 37% were boys) were included in the analyses. Conditional latent growth curve analyses were performed to test for the indirect effects on ED symptomatology and weekly frequency of protein- and creatine supplement use measured at the 12-month follow-up via change in the proposed mediators. Results: In girls, the reduction in ED symptomatology was mediated by positive changes in protective factors (self-esteem and body image flexibility), and reductions in risk factor scores (perceived media pressure and thin appearance internalization). Comparable changes in protective and risk factors among boys played no mediating role. Conclusion: Interventions designed to reduce the risk of ED development in girls may benefit from aiming to enhance self-esteem and body image flexibility and reduce perceived media pressure and thin appearance internalization. Future studies should investigate the causal relationship between muscle building supplement use and risk- and protective factors for ED development among both girls and boys.